Answer:
-5
Step-by-step explanation:
Let's find the answer by dividing [tex](-2m^{3}-m+m^{2}+1)[/tex] by [tex](m+1)[/tex], like this:
[tex](-2m^{2})*(m+1)=-2m^{3}-2m^{2}[/tex] and:
[tex](-2m^{3}-m+m^{2}+1)-(-2m^{3}-2m^{2})=3m^{2}-m+1[/tex] then:
[tex](3m)*(m+1)=3m^{2}+3m[/tex] and:
[tex](3m^{2}-m+1)-(3m^{2}+3m)=-4m+1[/tex] then:
[tex](-4)*(m+1)=-4m-4[/tex] and:
[tex](-4m+1)-(-4m-4)=5[/tex] notice that the remainder is 5 so we need to subtract the remainder.
Based on the previous procedure we can define:
[tex](-2m^{3}-m+m^{2}+1)/(m+1)=(-2m^{2}+3m-4) + 5[/tex]
In conclusion the smallest integer that can be added to the polynomial is -5, so the polynomial will be [tex](-2m^{3}-m+m^{2}-4)[/tex].